Serum Fructosamine and Glycated Albumin and Risk of Mortality and Clinical Outcomes in Hemodialysis Patients - Shafi, Tariq (American Diabetes Association, 2013)
OBJECTIVE: Assays for serum total glycated proteins (fructosamine) and the more specific glycated albumin may be useful indicators of hyperglycemia in dialysis patients, either as substitutes or adjuncts to standard markers such as hemoglobin A(1c), as they are not affected by erythrocyte turnover. However, their relationship with long-term outcomes in dialysis patients is not well described. RESEARCH DESIGN AND METHODS: We measured fructosamine and glycated albumin in baseline samples from 503 incident hemodialysis participants of a national prospective cohort study, with enrollment from 1995–1998 and median follow-up of 3.5 years. Outcomes were all-cause and cardiovascular disease (CVD) mortality and morbidity (first CVD event and first sepsis hospitalization) analyzed using Cox regression adjusted for demographic and clinical characteristics, and comorbidities. RESULTS: Mean age was 58 years, 64% were white, 54% were male, and 57% had diabetes. There were 354 deaths (159 from CVD), 302 CVD events, and 118 sepsis hospitalizations over follow-up. Both fructosamine and glycated albumin were associated with all-cause mortality; adjusted HR per doubling of the biomarker was 1.96 (95% CI 1.38–2.79) for fructosamine and 1.40 (1.09–1.80) for glycated albumin. Both markers were also associated with CVD mortality [fructosamine 2.13 (1.28–3.54); glycated albumin 1.55 (1.09–2.21)]. Higher values of both markers were associated with trends toward a higher risk of hospitalization with sepsis [fructosamine 1.75 (1.01–3.02); glycated albumin 1.39 (0.94–2.06)]. CONCLUSIONS: Serum fructosamine and glycated albumin are risk factors for mortality and morbidity in hemodialysis patients.